Danos do Cowpea mild mottle virus (CpMMV) e de moscabranca (Bemisia tabaci Genn.) no feijoeiro-comum geneticamente modificado resistente ao Bean golden mosaic virus - Santana, Marcus Vinícius (2015)
Common bean is susceptible to several viral diseases including Bean golden mosaic virus (BGMV) and Cowpea mild mottle virus (CpMMV). Since both viruses are whitefly transmitted, double infection can be easily overlooked due to the much intense BGMV symptomatology. The development of Embrapa 5.1 event of common bean resistant to BGMV (BGM), and near isogenic lines of two commercial cultivars (Pérola and BRS Pontal) allows the evaluation of the damage caused only by CpMMV, since these transgenic isolines do not get infected by BGMV. This study was conducted with the BGM to determine: 1) the damage caused by nymphs of B. tabaci in three phases of plant development; 2) the incidence and damage of CpMMV in correlation with the population of B. tabaci. The damage caused by six different densities of whitefly nymphs on BGM and conventional bean (CB) in the stages of primary leaves (V2), vegetative (V3-V4) and flowering (R6) were assessed in the greenhouse of Embrapa Rice and Beans. At the V2 stage were evaluated a mean number of 0, 20, 40, 60, 100 and 200 nymphs leaf-1; V3-V4 stage a mean number of 0, 40, 80, 130, 250 and 480 nymphs leaf-1 and at stage R6 a mean number of 0, 20, 50, 120, 280 and 760 nymphs leaf-1. The experimental design was completely randomized factorial of 6 x 2 (population levels of nymphs whitefly x BGM and FC), with 12 repetitions, except for the experiment in R6 with nine replicates. The experimental unit was represented by two bean plants. The incidence and severity of BGMV, the presence of sooty mold and yield components (number of pods, seeds per plant, seeds per pod, weight of grains) were determined. Field experiments were conducted in two experimental farms of Embrapa Rice and Beans in Santo Antônio de Goiás (16°30’24,57” S; 49°17’06,53” W) and Brazabrantes (16°26’09, 20” S, 49°24’05,80” W), State of Goiás. Four isolines derived from cv. Pérola, and six from cv. BRS Pontal, the two parental commercial cultivars, and three other entries named IPR Eldorado, BRB 169, and CNFC 15882 were compared. The incidence of BGMV, CpMMV, number of whitefly eggs, nymphs and adults were assessed as yield and yield components. The infestation of ≤ 200 nymphs of B. tabaci biotype B per leaf on primary leaves (V2), ≤ 480 nymphs per leaf in vegetative growth stage (V3-V4) and ≤ 760 nymphs per leaf in flowering stage (R6) not reduced grain yield per plant, number of pods per plant, and seeds per pod of CBGM. The BGMV affect the CB production at V2 and V3-V4 stages but not for R6 stage. The growth of the fungus Capnodium sp. (sooty mold) on the honeydew excreted by nymphs, was only observed on plants at V3-V4 stage. At field, the adult population of whiteflies was significantly lower in the GM lines derived from cv. Pérola (CNFCT 16201 and CNCF 16203) and from cv. BRS Pontal (CNFCT 16205), as well as on the commercial cv. IPR Eldorado, access BRB 169 and line CNFP 15882. It was not observed significant differences in whitely eggs and nymphs among the GM isolines and other bean genotypes. Despite the low incidence of CpMMV in the GM isolines derived from cv. Pérola, yield of these isolines was lower than that for some of the isolines derived from cv. BRS Pontal (CNFCT 16205, CNFCT 16206, CNFCT 16209 and CNFCT 16210) which had a higher incidence of CpMMV. At the Brazabrantes field a higher disease incidence was observed. The yield for cv. Pérola and BRS Pontal reached only 81 and 299 kg ha-1, respectively, and were significantly lower than the GM lines derived from cv. Pérola (711 kg ha-1) and cv. BRS Pontal (1073 kg ha-1). The low yield of the conventional common bean parental cultivars as compared to the GM isolines was due to the severe occurrence of BGMV. The GM isolines derived from cv. Pérola and from cv. BRS Pontal yielded an average of 878% and 358% higher, respectively, than the conventional accesses. The GM isolines have yield potential even at conditions of high incidence of B. tabaci and the CpMMV if a management program for whiteflies including cultural practices and insecticides is established.